Perspectives on current models of Friedreich’s ataxia - Kelekçi, Simge; Yıldız, Abdullah Burak; Sevinç, Kenan; Çimen, Deniz Uğurlu; Önder, Tamer (Frontiers in Cell and Developmental Biology, 2022)
Friedreich’s ataxia (FRDA, OMIM#229300) is the most common hereditary ataxia, which results from a reduction of Frataxin protein levels due to an expansion of GAA repeats in the first intron of FXN gene. Why the triplet repeat expansion causes a decrease in Frataxin protein levels are not entirely known. Generation of faithful FRDA disease models is crucial for answering questions regarding the pathophysiology of this disease. There have been considerable efforts to generate in vitro and in vivo models of FRDA. In this perspective article, we highlighted studies conducted using FRDA-animal models, patient-derived materials, and particularly induced pluripotent stem cells (iPSCs)-derived models. We discussed current challenges of using FRDA animal models, and patient-derived cells . Additionally, we provided a brief overview about how iPSCs-based models of FRDA were used to investigate the main pathways involved in disease progression, and to screen for a potential therapeutic agents for FRDA. Specific focus of this perspective article is to discuss the outlook and the remaining challenges in the context of FRDA iPSCs-based models.